Ceratodus tunuensis, sp. nov., a new lungfish (Sarcopterygii, Dipnoi) from the Upper Triassic of central East Greenland. Issue 2 (4th March 2018) - Agnolin, Federico L.; Mateus, Octávio; Milàn, Jesper; Marzola, Marco; Wings, Oliver; Adolfssen, Jan Schulz; Clemmensen, Lars B.
ABSTRACT: The fossil record of post-Paleozoic lungfishes in Greenland is currently restricted to a few brief reports of isolated and undetermined tooth plates coming from the uppermost Fleming Fjord Formation (late Norian) in Jameson Land, central East Greenland. Here, we describe Ceratodus tunuensis, sp. nov., a new dipnoan from a thin bed of calcareous lake mudstone from the Ørsted Dal Member of the Fleming Fjord Formation. The Ceratodus fossil record indicates that during the Late Triassic, this genus was restricted to the middle latitudes of the Northern Hemisphere. This record matches previous paleobiogeographical analyses and indicates that terrestrial biota during the Late Triassic was strongly influenced by paleolatitude. Citation for this article: Agnolin, F. L., O. Mateus, J. Milàn, M. Marzola, O. Wings, J. Schulz Adolfssen, and L. B. Clemmensen. 2018. Ceratodus tunuensis, sp. nov., a new lungfish (Sarcopterygii, Dipnoi) from the Upper Triassic of central East Greenland. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2018.1439834.